Edu-Generative Architecture an inclusive institution for early and middle childhood development in the Philippines - Commandante, Aaron Nicolai E.
This CDP addresses and tackles architectural and non-architectural problems in the current educational landscape of the Philippines through a proposal of an Inclusive Institution. Architectural problems include the lack of proper design interventions in current SPED schools in the Philippines, often leading to lack of focus, engagement, effectiveness, and overstimulation of children. Classrooms that are designed without the proper interventions causes limited opportunities for genuine collaboration, as well as the lack of individualized learning spaces which helps in the development of a child. There is a need for conducive and suitable learning environments for children with special needs and regular students. The Government, mainly due to funding, tend to underprioritize the quality of school buildings in the Philippines. This leads to the effectiveness of these schools towards childhood development. Non-architectural problems include the dependence of current schools in the Philippines on traditional teaching methods, the limited integration of technology for enhancing learning opportunities, and the high number of children with special needs in the Philippines. This is a CDP for a private SPED-Certified Institution in the Philippines that caters to both regular and with special needs children from Preschool to Grade 6, and will be emerging the learners with a new method for educational learning (i.e. Virtual Reality instruction technology) in classrooms. It is aimed at Early and Middle Childhood Development, with the school management focusing on the cognitive and behavioral growth and development aspect of these children. This CDP will only include limited cases of SPED learners with the following conditions: “moderate/severe cognitive disabilities”, “autism”, “learning disabilities”, “attention deficit”, and “behavioral disorders”. It is located in a corner lot in Quezon City’s 1st District’s barangay Bahay Toro, situated along Congressional Avenue and Jupiter Street. This CDP may Impact the field of Education by inspiring and directing the creations of facilities in the future, encouraging the use of leading-edge technologies to produce genuinely inclusive and groundbreaking learning environments of schools in the Philippines, contributing to future school Developments.